The Fate of Allogeneic Pancreatic Islets following Intraportal Transplantation: Challenges and Solutions - Xinyu Li; Qiang Meng; Lei Zhang (Journal of Immunology Research)
Pancreatic islet transplantation as a therapeutic option for type 1 diabetes mellitus is gaining widespread attention because this approach can restore physiological insulin secretion, minimize the risk of hypoglycemic unawareness, and reduce the risk of death due to severe hypoglycemia. However, there are many obstacles contributing to the early mass loss of the islets and progressive islet loss in the late stages of clinical islet transplantation, including hypoxia injury, instant blood-mediated inflammatory reactions, inflammatory cytokines, immune rejection, metabolic exhaustion, and immunosuppression-related toxicity that is detrimental to the islet allograft. Here, we discuss the fate of intrahepatic islets infused through the portal vein and propose potential interventions to promote islet allograft survival and improve long-term graft function.